Effect of ultrasound treatment on the emulsion gelling properties of PSE-like chicken myofibrillar protein - Chun-Lin Liu; Yan-Fang Zhou; He Zhu; Xiang-Li He; Ke Li (CyTA - Journal of Food)
The effects of ultrasound treatment (20 kHz, 0, 150, 300, 450, 600 W, 6 min) on the gel properties of PSE (pale, soft, and exudative)-like chicken myofibrillar protein (MP) emulsion gels were studied. When the ultrasound power increased from 0 W to 600 W, the water-holding capacity (WHC) and gel strength of PSE-like MP emulsion gel increased by 45.01% and 37.5%, respectively (p < 0.05), the storage modulus (G’) is increased and free water began to move in the direction of immobilized water, changed hydrogen bonds to other types of intermolecular force. Fourier transform infrared spectroscopy (FTIR) showed that ultrasound treatment promoted to the transformation from α-helix to β-sheet. The microstructure showed that the emulsion gel of MP after ultrasound treatment had a dense network structure. Ultrasound treatment effectively improved the gel properties of PSE-like chicken MP emulsion gels, which provides a new idea for improving the gel properties of PSE-like chicken protein.